Effect of tobacco smoking and alcohol consumption on semen quality and hormone reproductive levels in infertile males: A systematic review and meta analysis - Ryan Ramon; Syah Mirsya Warli; Nur Rasyid; Widi Atmoko (Pensoft Publishers, 2024)
Aim: This study compared semen quality, FSH, LH, and Testosterone levels in infertile males among smokers and non-smokers and semen quality among alcoholics and non alcoholics. Methods: A literature search was conducted across five databases in December 2021. The search for this article uses specific keywords tailored to each search database's specifications. Results: A total of 15 studies with 12,503 infertile male participants included in this study. 8,025 were non-smokers, 4,477 were smokers, 210 were alcoholics and 407 were non alcoholics. The effect of tobacco smoking on sperm were more significant in smokers than in non-smokers. Alcohol consumption affects the quality and quantity of semen. Both tobacco smoking and alcohol consumption combined may amplify their negative effects toward semen parameters. Conclusion: Smoking and alcohol has a detrimental impact on conventional semen characteristics. Due to the harmful effects of both factors, men seeking reproduction should be advised to avoid these habits.